Molecular characterization of Pasteurella multocida isolates from baemorrbagic septicaemia by ribotyping - ARORA, A K; JAND, S K; SANDHU, K S; OBEROI, M S (The Indian Journal of Animal Sciences, 2014)
Characterization of 17 isolates of Pasteurella multocida (serotype B:2) from haemorrhagic septicaemia in cattle and buffaloes was carried out by ribotyping. The phenotypic characteriz.ation of the isolates revealed that all the isolates were homogenous in their biochemical profiles. The DIG labelled probe used for ribotypin8 was derived from the PCR amplification of 16S rRNA gene of P multocida strain P52. Ribotyping with Pst I revealed complete homogeneity among the isolates whereas EcoR rand Hind in was able to distinguish the isolates into 2 different ribotypes each.